Detection and characterization of traumatic scalp injuries for forensic evaluation using computed tomography - Malli, Norbert; Ehammer, Thomas; Yen, Kathrin; Scheurer, Eva (International journal of legal medicine, 2013)
The purpose of this prospective study was to evaluate the rate of detection and correct classification of traumatic soft tissue injuries of the head using clinical multislice computed tomography (MSCT) compared with an external forensic examination. Thirty-one patients with soft tissue injuries after head trauma and clinically indicated cerebral MSCT scan underwent an external forensic examination with documentation of the morphological appearance and the exact localization of scalp and facial injuries. MSCT data were evaluated by a radiologist blinded to the results of the external examination using axial images as well as multiplanar reconstruction tools. The results of the radiological and forensic report were compared and analyzed. The main finding was that clinical MSCT data of the head detected 55 % of all external lesions and diagnosed the correct morphological type of lesion in 30 %. All lacerations and 44 % of the hematomas were correctly identified in the radiological report, whereas the diagnosis of swellings and abrasions was difficult. MSCT showed a high specificity for all types of soft tissue lesions. Additionally, a substantial number of internal lesions such as fractures or intracerebral bleedings were revealed which were not detected in the external examination. The results demonstrate that the forensic-radiologic evaluation of clinical MSCT data has a good diagnostic performance and is a valuable method to retrospectively supplement external forensic examination in living crime victims. It also might—to a certain extent—be used as the only source in cases where no forensic external examination has taken place within due time.